Protective effect of N-acetylcysteine against cisplatin ototoxicity in rats: a study with hearing tests and scanning electron microscopy - Somdaş,Mehmet Akif (2020)
Abstract Introduction Ototoxicity is a health problem appearing after powerful treatments in serious health conditions. It is sometimes inevitable when treatment of the serious disease is required. Cisplatin is an antineoplastic agent which was investigated previously to reveal increased nitrogen and reactive oxygen radicals that damages hair cells, resulting in ototoxicity. N-acetylcysteine, previously shown to decrease ototoxicity caused by different agents, is known to be a powerful in vitro antioxidant. Probably N-acetylcysteine, in addition to its antioxidant effect, blocks a cascade where reactive oxygen species result in apoptosis in the cochlea. Objectives The possible preventive effect of N-acetylcysteine in cisplatin ototoxicity was studied with auditory brain stem responses, otoacoustic emissions, and histopathological investigation of the cochlea in a scanning electron microscopy. Methods This study was conducted on 21 Wistar Albino rats in four groups. 1 mL/kg/day three times in total intraperitoneal (i.p.) Saline (n = 5), 500 mg/kg/day i.p. three times in total N-acetylcysteine (n = 5), i.p. 15 mg/kg cisplatin alone (single dose) (n = 5) and i.p. 15 mg/kg cisplatin plus 500 mg/kg/day N-acetylcysteine (n = 6) were administered. The rats were anesthetized to study the hearing tests before and after the experiment. The rats were sacrificed to investigate the cochleas by scanning electron microscopy. Results Auditory brain stem responses and otoacoustic emissions values were attenuated in the cisplatin group. The group that received N-acetylcysteine in addition to cisplatin had better auditory brain stem responses thresholds and otoacoustic emissions. The samples obtained from the cisplatin group showed surface irregularities, degeneration areas, and total or partial severe stereocilia losses. The changes were milder in the cisplatin + N-acetylcysteine group. Conclusion Cisplatin ototoxicity can be detected by auditory brain stem responses and otoacoustic emissions testing in rats. N-acetylcysteine may protect the cochlear cells from histopathological changes. We concluded that N-acetylcysteine given 4 h after cisplatin injection has a potential otoprotective effect against cisplatin ototoxicity. which suggests it could be used in clinical trials.